Optimasi PCR dengan Penanda Daerah D-loop DNA Mitokondria untuk Metode Tes DNA - Septiasari, Ni Putu Senshi; Junitha, I Ketut; Wirasiti, Ni Nyoman (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 2 (2022): Indonesian Journal of Legal and Forensic Sciences, 2022)
DNA testing is a molecular personal identification that can distinguish between individuals. One of the DNA markers used for PCR tests is mitochondrial DNA markers. Mitochondrial DNA is reported to have a polymorphic locus in the mitochondrial D-loop region. This study aims to determine the appropriate method to amplify mitochondrial DNA in the D-loop region for the DNA testing. A sample of 65 people was taken by purposive sampling method. Samples were extracted with phenol-chloroform and PCR with 2 types of PCR formulas, is formulas A and formulas B and the annealing temperatures used were 48 o C, 52 o C dan 56 o C.  The results showed that the optimal primary concentration for successful amplification was a Formulation B with primer concentration of 0,4 µM and condition variation II with annealing temperature of 52 o C. A total of 62 Balinese people were successfully amplified with an amplicon length of 860 bp. Samples that are not successfully amplified are affected by the number of collected epithelial cells, the success of the DNA extraction process and null allele. So, from these results it can be concluded that the optimal conditions of DNA marker with a primer concentration of 0,4 µM and annealing temperature  conditions of 52 o C succeeded in amplifying the D-loop region of mitochondrial DNA.